PENDIDIKAN PANCASILA DAN PEMBENTUKAN KESADARAN MORAL GENERASI MUDA - Heryanti Heryanti; Asti Wanda Rinjani (Penerbit Widina, Widina Media Utama, 2026)
Pancasila Education plays a strategic role in shaping the moral awareness of the younger generation amid rapid social, cultural, and technological changes. The challenges of globalization, digital media development, and shifting social values require strengthening value-based education rooted in national ideology. This article aims to analyze the role of Pancasila Education in fostering moral awareness among young people and to examine its relevance in contemporary social life. This study employs a literature review method by analyzing scientific articles, books, and previous research related to Pancasila Education, moral education, and character building. The findings indicate that Pancasila Education functions not only as a medium for transferring knowledge about national values but also as a means of internalizing moral values, ethics, and social responsibility. Through contextual and reflective learning approaches, Pancasila Education contributes to developing moral awareness reflected in attitudes of tolerance, justice, and social concern. In conclusion, strengthening adaptive Pancasila Education is essential for forming a morally grounded, value-oriented, and nationally committed young generation. ABSTRAKPendidikan Pancasila memiliki peran strategis dalam membentuk kesadaran moral generasi muda di tengah dinamika perubahan sosial, budaya, dan teknologi yang semakin kompleks. Tantangan globalisasi, perkembangan media digital, serta pergeseran nilai sosial menuntut adanya penguatan pendidikan nilai yang berakar pada ideologi bangsa. Tujuan penulisan artikel ini adalah untuk menganalisis peran Pendidikan Pancasila dalam menumbuhkan kesadaran moral generasi muda serta mengkaji relevansinya dalam konteks kehidupan sosial kontemporer. Metode yang digunakan adalah studi kepustakaan dengan menelaah berbagai literatur ilmiah, buku, dan hasil penelitian terkait Pendidikan Pancasila, pendidikan moral, dan pembentukan karakter. Hasil kajian menunjukkan bahwa Pendidikan Pancasila tidak hanya berfungsi sebagai wahana transfer pengetahuan tentang nilai-nilai dasar negara, tetapi juga sebagai sarana internalisasi nilai moral, etika, dan tanggung jawab sosial. Melalui pendekatan pembelajaran yang kontekstual dan reflektif, Pendidikan Pancasila mampu membangun kesadaran moral generasi muda yang tercermin dalam sikap toleransi, keadilan, dan kepedulian sosial. Kesimpulannya, penguatan Pendidikan Pancasila yang adaptif terhadap perkembangan zaman menjadi kunci dalam membentuk generasi muda yang bermoral, berkarakter, dan berkomitmen terhadap nilai-nilai kebangsaan.